(3CdajI ZQjH GdbQGfs - (3YHO GdQMje Hf GdMSjf Hf YHO GdQMef, CHh GdaVd, Rjf GdOjf, GdMGaX GdYQGbj, J (B806 (3g`s ((3YeQ Hf eMeO GdbGOQi s)
(3ChdgG (B:s
(3GdMeO ddg GJe GdMeO Ydi GjGO YXeJ Yf YO hHYO aGdYHO fhi Gf jfXeG ZQjH CdaGX GdbQGf YXeG LeY CHj MjGf hgh QJHg JQJjH MQha GdgLGA hgPHg s
(3BNQgG (B:s
(3hcedJ YfO GdShjS YGFOkG ef SaQi GdaVd QHi MGeOkG eUdjG Ydi fHi GdQMeI agh TajYi hgh di hSjJdi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3QVGQGeHhQ (B(487) s
Keywords: (3GddZIs